2015
DOI: 10.1016/j.jvs.2015.04.415
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Varenicline on Smoking Cessation Through Smoking Reduction: A Randomized Clinical Trial

Abstract: After adjusting for APACHE II scores, personal or family history of DVT, body mass index, vasopressor use, type of thromboprophylaxis, and presence of leg DVT, NLDVTs were associated with an increased risk of PE (hazard ratio, 11.83; 95% CI,). Nonleg NLDVTs were not associated with ICU mortality (hazard ratio, 1.09; 95% CI, 0.62-1.92) in a model that adjusted for age, APACHE II scores, vasopressor use, mechanical ventilation, renal replacement therapy, and platelet count below 50 Â 109/L.Comment: The data indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 0 publications
5
60
1
2
Order By: Relevance
“…In the present study, the effect of telling SLA on smoking quit rate was lost, considering the relapse rate at 1 year after successful quit on Visit 5: 21.4% (6/28) in the SLA group vs. 31.0% (9/29) in controls. Agboola et al demonstrated a 55% relapse after abstinence from smoking at week 52 among varenicline users (20), whereas Ebbert et al showed that abstinence rates from smoking among varenicline users were 32% during 15 through 24 weeks and 27% during 21 through 52 weeks (21). Compared to those reports, the relapse rates seemed to be lower in our study.…”
Section: Discussioncontrasting
confidence: 84%
“…In the present study, the effect of telling SLA on smoking quit rate was lost, considering the relapse rate at 1 year after successful quit on Visit 5: 21.4% (6/28) in the SLA group vs. 31.0% (9/29) in controls. Agboola et al demonstrated a 55% relapse after abstinence from smoking at week 52 among varenicline users (20), whereas Ebbert et al showed that abstinence rates from smoking among varenicline users were 32% during 15 through 24 weeks and 27% during 21 through 52 weeks (21). Compared to those reports, the relapse rates seemed to be lower in our study.…”
Section: Discussioncontrasting
confidence: 84%
“…All these aids were shown to be more effective than placebo [18][19][20] . In general, the results of this study follow the trend observed from previous literature with varenicline alongside with behavioural counselling appearing to be the most effective, with a 12-month point-prevalence abstinence rate of 34.3%.…”
Section: Tobacco Prevention and Cessationmentioning
confidence: 99%
“…It is known to be a blocker; however, it does have partial receptor activator properties; it penetrates the brain and stimulates dopamine release in the reward center. A study on the effect of varenicline for 6 months and one year on smoking cessation via smoking reduction, when compared to placebo was shown to drastically reduce smoking in participants [8,22,23,30,35]. …”
Section: Traditional Pharmacological Methodsmentioning
confidence: 99%